2011
DOI: 10.1128/aac.00637-11
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of Antifungal Agents within Host Cell Membranes: a New Paradigm Governing the Efficacy of Prophylaxis

Abstract: Posaconazole prophylaxis has proven highly effective in preventing invasive fungal infections, despite relatively low serum concentrations. However, high tissue levels of this agent have been reported in treated patients. We therefore hypothesized that the intracellular levels of antifungal agents are an important factor in determining the success of fungal prophylaxis. To examine the effect of host cell-associated antifungals on the growth of medically important molds, we exposed cells to antifungal agents an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
57
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 31 publications
9
57
0
4
Order By: Relevance
“…Notably, the posaconazole-treated cells were found to resist infection by A. fumigatus 14,18 The protective effect of cell-associated posaconazole persisted for at least 48 h after removal of free drug. 18 Measurement of posaconazole kinetics in epithelial cells demonstrated that this prolonged post-antifungal effect was due to the persistence of high levels of drug within the epithelial cells, 18 thus providing an explanation for the prolonged post-antifungal effect reported in animal studies of posaconazole. 12 In addition, cellular fractionation experiments and localization studies using fluorophore-conjugated posaconazole have demonstrated that this hydrophobic antifungal accumulates only within membrane compartments of host cells, rather than throughout the whole cell.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Notably, the posaconazole-treated cells were found to resist infection by A. fumigatus 14,18 The protective effect of cell-associated posaconazole persisted for at least 48 h after removal of free drug. 18 Measurement of posaconazole kinetics in epithelial cells demonstrated that this prolonged post-antifungal effect was due to the persistence of high levels of drug within the epithelial cells, 18 thus providing an explanation for the prolonged post-antifungal effect reported in animal studies of posaconazole. 12 In addition, cellular fractionation experiments and localization studies using fluorophore-conjugated posaconazole have demonstrated that this hydrophobic antifungal accumulates only within membrane compartments of host cells, rather than throughout the whole cell.…”
mentioning
confidence: 98%
“…12 In addition, cellular fractionation experiments and localization studies using fluorophore-conjugated posaconazole have demonstrated that this hydrophobic antifungal accumulates only within membrane compartments of host cells, rather than throughout the whole cell. 18,19 Because membranes represent only a small fraction (<10%) of the volume of eukaryotic cells, the actual membrane concentration of posaconazole is at least 10-fold higher than prior estimates of total cellular concentration. Thus the membrane concentrations of posaconazole can reach levels as high as 400-fold greater than those found in the serum.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…After previous research had suggested that intracellular levels of posaconazole may be more relevant to therapeutic efficacy than serum levels [24], Campoli et al observed that posaconazole was predominantly found in host cell membranes in concentrations sufficient to inhibit growth and prevent fungal damage [25]. Subsequent research, presented at ECCMID, showed that during infection, posaconazole transferred from host cell membranes to fungal membranes and was concentrated within the endoplasmic reticulum (ER) [26].…”
Section: Update On Af Treatmentmentioning
confidence: 99%
“…95 It has been found that posaconazole penetrates alveolar cells and monocytes in concentrations that far exceed the blood, and this finding may be the explanation for why posaconazole is effective in preventing IFI despite low serum levels. 102 With regard to therapeutic efficacy, a target concentration of at least 1 mg/L has been proposed and is based on the study by Walsh et al that showed improved clinical response rates with higher posaconazole levels in patients with established IFI on salvage therapy. 103 It is unknown how feasible it would be to attain and/or maintain such a level in practice.…”
Section: Therapeutic Drug Monitoringmentioning
confidence: 99%